2023
DOI: 10.1101/2023.01.19.524677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Propionate reinforces epithelial identity and reduces aggressiveness of non-small cell lung carcinoma via chromatin remodelling

Abstract: Epithelial to mesenchymal transition (EMT) is a developmental cellular program driving metastasis and chemo-resistance in cancer, but its pharmacological treatment has been so far challenging. Targeting deregulated metabolic processes in cancer is emerging as a realistic therapeutic strategy. Here, we used an EMT-focussed integrative functional genomic approach and identified negative association of the short-chain fatty acids, propionate and butanoate, with EMT in non-small cell lung cancer (NSCLC) patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Furthermore, to examine the associations pattern at a single cell expression level, a single cell RNA sequencing of parental A549 cell line (untreated) was explored from our previous study (Ramesh et al , 2023), and the analysis revealed a consistent results of positive and negative association of the pathways with the pyrimidine metabolism across 5,203 cells ( Figure 2G ). Remarkably, a cluster-based analysis showed that pyrimidine and its associated positive signaling pathways or metabolic processes were strongly expressed in cluster 1 ( Figure 2H and Supplementary Figure S2D ).…”
Section: Resultsmentioning
confidence: 87%
“…Furthermore, to examine the associations pattern at a single cell expression level, a single cell RNA sequencing of parental A549 cell line (untreated) was explored from our previous study (Ramesh et al , 2023), and the analysis revealed a consistent results of positive and negative association of the pathways with the pyrimidine metabolism across 5,203 cells ( Figure 2G ). Remarkably, a cluster-based analysis showed that pyrimidine and its associated positive signaling pathways or metabolic processes were strongly expressed in cluster 1 ( Figure 2H and Supplementary Figure S2D ).…”
Section: Resultsmentioning
confidence: 87%